2015
DOI: 10.1109/tsg.2015.2497339
|View full text |Cite
|
Sign up to set email alerts
|

Online Coordinated Voltage Control in Distribution Systems Subjected to Structural Changes and DG Availability

Abstract: The responses of multiple DG units and voltage regulating devices such as tap changers and capacitor banks for correcting the voltage may lead to operational conflicts and oscillatory transients, where distribution systems are subjected to network reconfiguration and changes in availability of the DG units. Therefore, coordinated voltage control is required to minimize control interactions while accounting for the impact of structural changes associated with the network. This paper proposes a strategy for coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Methods can operate in real-time based on measurements or state estimation data (e.g. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]) or predetermine a control schedule for the controllable resources based on forecasted load and production (e.g. [18][19][20][21]) or combine the two approaches [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods can operate in real-time based on measurements or state estimation data (e.g. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]) or predetermine a control schedule for the controllable resources based on forecasted load and production (e.g. [18][19][20][21]) or combine the two approaches [22].…”
Section: Introductionmentioning
confidence: 99%
“…In centralised methods (e.g. [2][3][4][5][6][7][8][9][10][11][12][13]), measurement data is gathered to one point in the network (usually the control centre), control decisions are made based on that data and control commands are then sent to the controllable resources. The advantages of centralised methods are that they can take into account the whole network when determining the control actions and that they can be relatively easily integrated into existing systems of distribution system operators (DSOs).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to cloud transients, PV power can fluctuate more quickly and frequently than customer loads [9]. As a result, SVRs may suffer from excessive tap changes.Currently, there are two main categories of research on tap operations in the solar PV integration area: 1) interaction between solar PV systems and tap operations (PV-Tap) [10][11][12]; 2) coordinated voltage control of PV inverters and voltage regulators (e.g., SVR, OLTC) to mitigate excessive tap operations caused by PV power fluctuations [13][14][15]. However, these researches mostly involve theoretical studies based on simulation, and the use of actual tap positions is rare since tap positions are usually not accessible to customers.…”
mentioning
confidence: 99%
“…A common approach to control coordination is based on rule-based algorithms as demonstrated in [35], [36], [37] or [38]. Those algorithms deliberately enforce interaction between voltage regulating devices.…”
Section: A) Control Coordination Without Optimisationmentioning
confidence: 99%
“…Interestingly though, study [35] elaborates on using sensitivity matrix not for control calculation purposes but rather to determine how to split a system into smaller areas with limited impact on each other. Nonetheless, it has been found that sensitivity analysis has its limitations, which strongly affect coordination schemes.…”
Section: Figure 25 Example Of Non-optimised Control Coordinationmentioning
confidence: 99%